Spawning habitat selection by the common cuttlefish Sepia officinalis in the Cíes Islands (Northwest Spain) - Guerra, Ángel (2016)
We evaluated specific habitat features (bottom substrate type, depth, temperature, season and latitude- longitude) at random locations in the Cíes Islands (Galician Atlantic Islands National Park, Northwest Spain) to determine their impact on Sepia officinalis spawning habitat use. We performed underwater visual transects via scuba diving. In total, 94 transects were conducted between April 30, 2012 and July 17, 2015. Habitat features were evaluated as predictors of the presence/absence of egg clusters using Generalised Additive Models. Statistical analyses revealed the following: (a) the probability of finding eggs was significantly higher on hard bottom substrate type containing sea fans and sea tube worms; (b) thesectorswheretheeggpresencewashighestwerethemostshelterszonesofBajodeVin ̃osandPiedra del Borrón, two hard bottom shoals covered by sea fans and sea worms and located in the central Cíes Islands or Faro Island; (c) The preferential depth ranged from 8 to 13 m; (d) as temperatures rose, the probability of finding eggs decreased, which was a sign of the seasonality of the spawning event of the species; and (e) eggs were most common in the winter. A total of 18 additional non-random underwater visual transects were then performed in the Vin ̃os and Borrón shoals between December 10, 2014 and August 20, 2015. We calculated the number of egg clusters found in two fenced areas (0.04 ha) located in Vin ̃os and Borrón, which showed that Vin ̃os was a most suitable spawning habitat than Borrón. The number of eggs per cluster varied from 4 to 82. The spawning period for this species lasted from the beginning of December until the end of June, when bottom temperature ranged from 12.5 ◦ C to 14.75 ◦ C. These microhabitat data reveal indicators of common cuttlefish spawning habitat utilisation and should help identify targets for habitat improvement projects and ecosystem management approaches within this national park and elsewhere.